“Reacondicionamiento de las instalaciones eléctricas de baja tensión para la escuela de educación básica rio san pablo del toquillal”. - Chanaluisa Flores, Wagner Iván (2022)
In the present project, the electrical system of the basic education school of Toquillal in the La Mana canton was analyzed, which showed faults such as: bad connection from the connection, deterioration in the cable and connection, sulfated cables, incorrect category of the same. and in many cases carrying out clandestine splices with twin cable. All this caused major failures and overload when placing many loads. Bare cables without the necessary insulation were also shown for the lighting circuits, which on many occasions caused electric shocks to people and children who had the misfortune to touch them unintentionally. The lack of a distribution box for the independent control of lighting systems, outlets or special loads was also identified. Having recognized all this problem, we proceeded to solve it, firstly, changing the cable that comes from the connection, removing all the deteriorated elements: cables, gutters, hoses, switches, outlets. Then, new elements were placed according to the NEC Standard for Electrical Installations with two distribution boxes since there are two blocks that make up the school with 3 electrical circuits: for lighting, outlets and special loads. Achieving with this to maintain a constant energy supply from its readjustment to the present.